Prickly Pear Betalain-Rich Extracts as New Promising Strategy for Intestinal Inflammation: Plant Complex vs. Main Isolated Bioactive Compounds - Smeriglio, A.; De Francesco, C.; Denaro, M.; Trombetta, D. (Frontiers in Pharmacology, 2021)
Recently, many studies have highlighted the health effects of betalains beyond their use as food dyes. The present study investigated betalain-rich extract with different colours and their main bioactive compounds in order to provide first evidences as new promising strategy for intestinal inflammation management. Prickly pear betalain-rich extracts, obtained by a QuEChERS method, have been characterized by LC‐DAD‐ESI-MS/MS analysis. The potential role of betanin, indicaxanthin and prickly pear extracts in counteract the antioxidant and anti-inflammatory events were evaluated by several in vitro cell-free and cell-based assays. Indicaxanthin and betanin represent the most abundant compounds (≥ 22.27 ± 4.50 and 1.16 ± 0.17 g/100 g dry extract, respectively). Prickly pear extracts showed the strongest antioxidant and anti-inflammatory activity with respect to the pure betalains both on in vitro cell-free and cell-based assays, demonstrating the occurrence of synergistic activity, without any cytotoxicity or alteration of the barrier systems. The release of reactive oxygen species (ROS) as well as of key inflammatory markers (IL-6, IL-8 and NO) was strongly inhibited by both betalains and even more by prickly pear extracts, which showed a similar and sometimes better profile than the reference compounds trolox and dexamethasone in counteracting the IL-1 β-induced intestinal inflammation.